EVALUASI KEMITRAAN ANTARA PETANI TEBU DAN PT PERKEBUNAN NUSANTARA VII UNIT USAHA BUNGA MAYANG, KECAMATAN BUNGA MAYANG, KABUPATEN LAMPUNG UTARA - Iqbal Lazuardi Pranoto; Dyah Aring Hepiana Lestari; Ktut Murniati (Lampung University, 2017)
The purpose of this study was to evaluate the implementation of the partnership, analyze the factors that affected farmers' decision on joining partnership, analyze the differences of on farm income of partner farmers and non-partner farmers, and analyze the satisfaction of partner farmers to the implementation of the partnership at PTPN VII Bunga Mayang. This research was conducted purposively in the village of Iso Rejo and Penagan Ratu. The data was collected from August to November 2016. Respondents were 77 partner farmers that were selected by simple random sampling and all 20 non-partner farmers. Data were analyzed by descriptive statistic analysis and regression analysis. The result obtained from this study showed that the overall implementation of the partnership was in accordance with the contract that had been agreed by both sides. Factors that affected farmers' decision to join the partnership in PTPN VII Bunga Mayang were education and income per hectare. Sugarcane farming income of partner farmers were greater than non-partner farmers. Satisfactions of partner farmers to the implementation of the partnership as a whole was on the criteria of